2010
DOI: 10.1002/asia.201000628
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy Investigation of Copper Phthalocyanine and Truxenone Derivative Binary Superstructures on Graphite

Abstract: The binary self-assembly of copper phthalocyanine (CuPc) and 2,3,7,8,12,13-hexahexyloxy-truxenone (TrO23) at the solid/liquid interface of highly oriented pyrolytic graphite (HOPG) was investigated by using scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS). Pseduohexagonal and linear patterned superstructures of CuPc are obtained by co-adsorbing with TrO23. High-resolution STM images reveal the structural details of the arrangement of TrO23 and CuPc in the binary assembly structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In other words, the weak interaction between CuPc separators and TBU lobes is compensated by desolvation energy of CuPc at the solid/liquid interface. A similar solvent effect to modulate the self-assembly has been observed in other systems. By increasing the concentration of TCDB in the solution phase, and thus the coverage of it on the surface, the lobes grow bigger and form hierarchical structures with higher generations. At high coverage and suitable molar ratio of TCDB and TrO23, Flower 0 is preferred since the center-sitting TCDB provides extra hydrogen bonding to stabilize the structure.…”
Section: Resultsmentioning
confidence: 54%
“…In other words, the weak interaction between CuPc separators and TBU lobes is compensated by desolvation energy of CuPc at the solid/liquid interface. A similar solvent effect to modulate the self-assembly has been observed in other systems. By increasing the concentration of TCDB in the solution phase, and thus the coverage of it on the surface, the lobes grow bigger and form hierarchical structures with higher generations. At high coverage and suitable molar ratio of TCDB and TrO23, Flower 0 is preferred since the center-sitting TCDB provides extra hydrogen bonding to stabilize the structure.…”
Section: Resultsmentioning
confidence: 54%
“…Although the electrochemical deposition of [CoTmtppa] 4+ onto various electrode surfaces was previously studied in detail, ,, nothing is known about the spontaneous adsorption onto a conducting substrate. Undoubtedly, it will have an apparent advantage against electrochemical as well as vacuum deposition, , because these require an additional energy supply, while still preserving the homogeneity of spontaneously formed layers. , As graphite/graphene is nowadays the electronic material of choice in the above-mentioned applications, we focused on the spontaneous adsorption of [CoTmtppa] 4+ on HOPG (whereas a graphene C 150 -cluster was used as a theoretical model for the HOPG basal plane). EPR spectroscopy is a suitable technique for surface analysis, because it can provide direct qualitative and quantitative evidence of the unpaired electron (spin) distribution on a surface, which cannot be acquired by common surface methods.…”
Section: Introductionmentioning
confidence: 99%
“…23 Mixing 2,3,7,8,12,13hexahexyloxy-truxenone (TrO23) with copper phthalocyanine (CuPc) or 1,3,5-tris(R-carboxydecyloxy)benzene (TRCDB, R = different alkyl chain), TrO23 assembled into molecular lines or networks depending on types and concentrations of other components. 24,25 Further study indicated that the chirality in the basic structure motif formed with numbers of T10CDB (TRCDB, R = 10), TrO23 and CuPc molecules was kept and amplified in following hierarchical structures. 26 For cyanobenzyl modified truxene, only those adsorbing on surface kinks and edges are stable enough to be observed with non-contact atomic force microscopy due to high diffusion energy barriers at those positions.…”
Section: Introductionmentioning
confidence: 99%